Development and Validation of “Hazard O’Clock”: A Home Hazard and Disaster Awareness Game - Penus, Reynal M. (Animo Repository, 2022)
The Philippines is the fourth most disaster-prone country in the world due to its location in the Pacific Ring of Fire and Pacific Typhoon Belt. When it comes to these disasters, children below the age of 18 are considered to be among the most vulnerable. This study aimed to develop a mobile game about Disaster Risk Reduction and Management (DRRM) in the home setting that can be used as a teaching aid for children. The information integrated into the game was from different resources made by various government agencies. The Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model was used in the development of the game, and game development educators and STEM educators evaluated it. Using a 5-point Likert scale survey, the game’s quality and appropriateness were evaluated for the following categories: Instructional Content, Functional Suitability, Performance Efficiency, and Usability. For each category, the mean score ratings were 4.43, 4.43, 4.80, and 4.60 respectively. Overall, the game received a rating of 4.52 indicating that it is Very Appropriate for its purpose. The research findings have shown that the game, Hazard O’Clock, could be used as a teaching aid for DRRM.